Composition and Community Structure of Plant Species in A Secondary Growth Forest in the Central Philippines (Journal of Biodiversity Conservation and Bioresource Management, 2023)
Mt. Bandila-an Forest Reserve (MBFR) is among the remaining areas with patches of closed forests in Siquijor. This forest reserve is one of the potential key biodiversity areas in Central Visayas, yet the vegetation is not fully documented. This study was conducted to determine the species composition and diversity of plant species. Eight randomly distributed nested plots, each with a dimension of 20m×100m and subdivided to 5 equal segments of 20m×20m, were established. A total of 188 plant species was recorded from the plots, representing 131 tree species, 23 shrub, 14 vine, 11 herb, and 9 fern species. Common plant families with more than 6 representative species were Moraceae, Rubiaceae, Fabaceae, Araceae, Euphorbiaceae, Meliaceae and Myrtaceae. There were 19 threatened (vulnerable to critically endangered) and 33 endemic species recorded in the forest reserve highlighting the importance to further conserve the area. The cluster analysis and species accumulation curve suggest that plant species are not homogeneously distributed which implies that different management and conservation strategies should be implemented across MBFR. These results not only indicate the importance of MBFR, but also highlight areas with higher diversity and concentration of threatened and endemic species as a special area of concern.J. Biodivers. Conserv. Bioresour. Manag. 2023, 9(1): 13-28